Antibacterial Activity of a Cardanol from Thai Apis mellifera Propolis - Boonsai, Pattaraporn (Ivyspring International Publisher, 2014)
Background: Propolis is a sticky, dark brown resinous residue made by bees that is derived from plant resins. It is used to construct and repair the nest, and in addition possesses several diverse bioactivities. Here, propolis from Apis mellifera from Nan province, Thailand, was tested for antibacterial activity against Gram(+ve) (Staphylococcus aureus and Paenibacillus larvae) and Gram(-ve) (Escherichia coli) bacteria. Materials and methods: The three bacterial isolates were confirmed for species designation by Gram staining and analysis of the partial sequence of 16S rDNA. Propolis was sequentially extracted by methanol, dichloromethane and hexane. The antibacterial activity was determined by agar well diffusion and microbroth dilution assays using streptomycin as a positive control. The most active crude extract was further purified by quick column and adsorption chromatography. The apparent purity of each bioactive fraction was tested by thin layer chromatography. The chemical structure of the isolated bioactive compound was analyzed by nuclear magnetic resonance (NMR). Results: Crude methanol extract of propolis showed the best antibacterial activity with a minimum inhibition concentration (MIC) value of 5 mg/mL for S. aureus and E. coli and 6.25 mg/mL for P. larvae. After quick column chromatography, only three active fractions were inhibitory to the growth of S. aureus and E. coli with MIC values of 6.25 and 31.3 µg/mL, respectively. Further adsorption chromatography yielded one pure bioactive fraction (A1A) with an IC(50) value of 0.175 µg/mL for E. coli and 0.683 µg/mL for P. larvae, and was determined to be cardanol by NMR analysis. Scanning and transmission electron microscopy analysis revealed unusual shaped (especially in dividing cells), damaged and dead cells in cardanol-treated E. coli. Conclusion: Thai propolis contains a promising antibacterial agent.